2015
DOI: 10.1017/s147895151500022x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing student communication during end-of-life care: A pilot study

Abstract: Simulation was found to be an effective means of preparing students to communicate with dying patients and their families. The opportunity to develop communication skills was valued. Integration of educational interventions employing simulated patient actors into nursing and medical curricula may assist in improving the care provided to patients at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Regarding interventions to improve patient-centered communication skills of nursing students, it was observed that the majority focused on simulation, using SP (e.g., [26,32,33]), role-playing [39] or high-fidelity patient [34], to either facilitate learning or evaluate communication skills. Previous studies indicate the importance of incorporating simulation in communication skills training.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding interventions to improve patient-centered communication skills of nursing students, it was observed that the majority focused on simulation, using SP (e.g., [26,32,33]), role-playing [39] or high-fidelity patient [34], to either facilitate learning or evaluate communication skills. Previous studies indicate the importance of incorporating simulation in communication skills training.…”
Section: Discussionmentioning
confidence: 99%
“…Design: quasi-experimental study, two gropup study. [32] (UK) 2D n = 28 second-year nursing students and fourth-year medical students from a population of N = 180 nursing students and N = 450 medical students.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations